2014
DOI: 10.7314/apjcp.2014.15.8.3757
|View full text |Cite
|
Sign up to set email alerts
|

Is the Tumor Infiltrating Natural Killer Cell (NK-TILs) Count in Infiltrating Ductal Carcinoma of Breast Prognostically Significant?

Abstract: Asian Pac J Cancer Prev, 15 (8), 3757-3761 IntroductionBreast cancer is the most common cause of cancer death in women worldwide (Key et al., 2001), and represents the leading or second most leading cancer in females in India (Ferlay et al., 2010;D'Souza et al., 2013a;2013b). Currently, two major challenges of breast cancer research are; to understand the interrelation between breast cancer and anti-tumor immunity, and to identify candidates whose targeting would contribute to enhance anti-tumor efficiency (Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…These results suggested that MCT4‐induced NK cell activation and acidosis of the tumor microenvironment are regulated by an MCT4‐dependent lactate flux in the 4T1 cell line. In addition, we discovered by IHC that the activities of the NK cells also decreased in mouse breast cancer tissues, and this finding is consistent with a previous report . Based on the principles outlined in the Reverse Warburg Effect hypothesis, glycolysis and lactate can be conducive to the growth of tumor cells .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results suggested that MCT4‐induced NK cell activation and acidosis of the tumor microenvironment are regulated by an MCT4‐dependent lactate flux in the 4T1 cell line. In addition, we discovered by IHC that the activities of the NK cells also decreased in mouse breast cancer tissues, and this finding is consistent with a previous report . Based on the principles outlined in the Reverse Warburg Effect hypothesis, glycolysis and lactate can be conducive to the growth of tumor cells .…”
Section: Discussionsupporting
confidence: 92%
“…In addition, we discovered by IHC that the activities of the NK cells also decreased in mouse breast cancer tissues, and this finding is consistent with a previous report. 36 Based on the principles outlined in the Reverse Warburg Effect hypothesis, glycolysis and lactate can be conducive to the growth of tumor cells. [37][38][39] It has been previously established that the antitumor activities of NK cells are impaired by hypoxia, acidosis, and glucose metabolic abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that these altered NK cells directly reduce the number of T cells in the tumour microenvironment, thus also inhibiting the immune response to tumours . The notion of a possible tumour‐promoting function of NK cells is supported by the finding of an association between increased NK‐cell infiltration and poorer outcome in metastatic ovarian carcinoma and invasive ductal carcinoma of the breast .…”
Section: The Immune System and Its Therapeutic Targeting In Anticancementioning
confidence: 99%
“…Under the influence of cytokines and chemokines secreted by the cancer cells, fibroblasts phenotypically change into cancer-associated fibroblasts (CAFs), macrophages are activated and attracted toward the tumor environment (tumor-associated macrophages [TAMs]), and lymphocytes infiltrate the tumor (tumor-infiltrating lymphocytes [TILs]). These CAFs, TAMs, and TILs exert tumor-stimulating or tumor-protective actions, are involved in therapy resistance, and are linked with breast cancer prognosis [4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%